Vegetables contamination by Parasitic Helminth Eggs in Malaysia and Indonesia - Reashnaa Loganathan; Ridad Agoes; Insi Farisa Desy Arya (Faculty of Medicine Universitas Padjadjaran, 2016)
Background: Soil-transmitted helminth infection is known to be a serious issue in South East Asia when the farmers use night soil and contaminated water for their plants. In Indonesia, some of the farmers still use human feces and sometimes also mixed it with urine from the latrines as fertilizers. On the contrary, in Malaysia these contamination occured at a lower rate due to strict rules by the authorities.The objective of this study was to identify the helminth eggs in vegetables from traditional markets in Indonesia and Malaysia.Methods: Three traditional markets were selected by non-random sampling, namely Pasar Ampang in Malaysia and 2 traditional markets in Indonesia, i.e Pasar Tanjungsari and Jatinangor. Cabbages and lettuce were bought from 15 different vegetable sellers per market. The samples were examined at the laboratory of the Medical Faculty, Universitas Padjadjaran. The method to obtain the specimen was in accordance with Khairul Anwar and Ramachandran. This study was carried out from July to October 2014. The collected data was analyzed by percentage and frequency tabulation.Result: Most of the samples are contaminated by helminth eggs. In Pasar Ampang, 13.3% in cabbage and 6.7% in lettuce. In Pasar Tanjung Sari, 46.7% in cabbage and 40% in lettuce. Moreover, in Pasar Jatinangor, 33.3% in cabbage and 26.7% in lettuce. Most of the helmint eggs were Ascaris lumbricoides.Conclusions: The helminthes eggs contamination is higher in Indonesian traditional markets compared to in Malaysia. [AMJ.2016;3(2):190–4]DOI: 10.15850/amj.v3n2.796